2007
DOI: 10.1128/aem.01225-07
|View full text |Cite
|
Sign up to set email alerts
|

Different Genotypes of Anatoxin-Producing Cyanobacteria Coexist in the Tarn River, France

Abstract: The cyanobacterial neurotoxic alkaloid anatoxin-a and/or its methyl homolog, homoanatoxin-a, was detected in the extracts of most samples examined by gas chromatography-mass spectrometry. Fifteen filamentous cyanobacteria of the order Oscillatoriales were isolated and displayed four distinct phenotypes based on morphological characteristics and pigmentation. Three of the phenotypes can be assigned to the genus Oscillatoria or Phormidium, depending on the taxonomic treatises (bacteriological/botanical) employed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
87
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(90 citation statements)
references
References 35 publications
1
87
0
2
Order By: Relevance
“…In this study, we found no correlation between the coverage of Phormidium mats and ATX and/or HTX concentrations. Previous investigation have shown that cyanobacterial mats consist of mixed toxic and non-toxic strains of Phormidium autumnale (Cadel-Six et al 2007. It is possible that the variations in ATX and/or HTX concentrations observed in this study were due to changes in the relative abundances of toxic and non-toxic Phormidium strains in a mat, rather than changes in the amount of ATX and/or HTX produced.…”
Section: Spatial and Temporal Variation In Anatoxin-a And Homoanatoximentioning
confidence: 38%
See 1 more Smart Citation
“…In this study, we found no correlation between the coverage of Phormidium mats and ATX and/or HTX concentrations. Previous investigation have shown that cyanobacterial mats consist of mixed toxic and non-toxic strains of Phormidium autumnale (Cadel-Six et al 2007. It is possible that the variations in ATX and/or HTX concentrations observed in this study were due to changes in the relative abundances of toxic and non-toxic Phormidium strains in a mat, rather than changes in the amount of ATX and/or HTX produced.…”
Section: Spatial and Temporal Variation In Anatoxin-a And Homoanatoximentioning
confidence: 38%
“…These events have commonly been linked to ingestion of toxins produced by planktonic Cyanobacteria (Negri et al 1995, Kuiper-Goodman et al 1999, Saker et al 1999, Azevedo et al 2002. However, animal toxicosis linked to benthic Cyanobacteria has increased recently (Mez et al 1997, Hamill 2001, Gugger et al 2005, Cadel-Six et al 2007, Wood et al 2007. The physical, chemical, and biological parameters leading to planktonic cyanobacterial blooms have been extensively studied (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Since ITS differences reflect the geographic distribution of cyanobacteria, as has been reported for aquatic strains (18,52), more ITS sequences of subaerophytic Leptolyngbya strains are needed to better understand their evolution and biogeography. To our knowledge, this is the first study in which a polyphasic approach, combining morphological and ultrastructural observations with 16S rRNA gene and ITS sequencing, was employed to resolve the diversity of Leptolyngbya strains and to assess intraspecific variation.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular approaches to the study of cyanobacterial systematics have focused primarily on the analysis of 16S rRNA gene sequences (57); however, this gene is highly conserved, and its use in estimating relationships at the subgeneric level is limited (24). On the other hand, the ITS region, which is more variable than the 16S rRNA gene and less subject to selection pressure, is considered a useful tool in cyanobacterial taxonomy (12,14,18,23,37,43). All these data allowed the successful identification of two phylotypes among six members of the genus Leptolyngbya and highlighted their intraspecific genetic variation.…”
mentioning
confidence: 99%
“…It is thus important to develop methodologies to detect these toxic microorganisms in water reservoirs, and so far, PCRbased amplification of genes responsible for the biosynthesis of these toxins is the best method (1). We have been interested in the study of cyanobacteria producing the neurotoxins anatoxin-a and homoanatoxin-a (2,17,18). Our goals were first to identify the genes responsible for the biosynthesis of these toxins and to deepen our knowledge of this interesting group of bacteria.…”
mentioning
confidence: 99%